Возрастная структура ценопопуляций Festuca valesiaca Gaudin и Festuca rupicola Heuff. в искусственных степных фитоценозах - Ибатулина, Ю.В. (Промышленная ботаника, 2003)
Behavior of the species in phytocenosis at the level of coenopopulations, individuals age states, cenopopulations age structure and type, seasonal dynamics of age structure have been examined. Almost all of cenopopulations can be regarded as young normal temporary having incomplete set of individuals left-sided by age composition ones, capable of self-regulating their structure. Seasonal changes are reported to affect the youngest part of coenopopulations most strongly, reducing its number.